Public Health Action Plan for the English-Speaking Community in the Capitale-Nationale Region 2011-2015 - Jeffery Hale - Saint Brigid's (JHSB) (2011)
Saint Brigid’s – Jeffery Hale Hospital’s Public Health Action Plan for the English- Speaking Community in the Capitale-Nationale Region is in keeping with the Plan d’action regional (PAR) en santé publique 2009-2012 (regional public health action plan) developed by the Agence de la santé et des services sociaux de la Capitale-Nationale (Agence). To ensure viable results for our efforts aimed at improving the health and well-being of the English-speaking community, we thought it relevant to begin by presenting an updated portrait of the English-speaking community in the CNR. This portrait allows us to identify the various needs of the community, as well as its health determinants and indicators, and take stock of its ongoing evolution. This description is followed by a detailed presentation of Saint Brigid’s – Jeffery Hale Hospital’s prevention and health promotion Service Offer.

Membership Socio-demographic Attributes 2010-11 - Voice of English-speaking Quebec (VEQ) (2011)